Challenges in clinical performance of dentistry clinicians: towards strengthening areas of outcomes or competencies - Laguna, Arvin Bullon (11th International Scholars Conference, 2019)
The study investigated the phenomenon of challenges and difficulties in the clinical performance of students in a university, accounting for the frequency of weaknesses and errors of clinician students during clinical training as observed by the faculty in terms of their knowledge, practical skills and attitudes. All eighteen faculty clinical consultants who were supervising the 7 Clinical Departments in the College of Dentistry in a university were invited to participate in the study, wherein questionnaires were given in two stages to identify and recall the frequency of occurrence of errors or weaknesses in the clinical performance of student clinicians in the 3rd and 4th year proper levels of the Dentistry Program. The seven Clinical Departments included the Restorative Dentistry Department, Oral Diagnosis Department, Periodontics Department, Oral Surgery Department, Endodontics Department, Prosthodontics Department, and the Pediatric Dentistry Department. The findings revealed several errors or weaknesses in clinical performance of students and some of these weaknesses were seen by the clinical consultants to be frequently performed. Some of these are critical in the proper training of future dentists and thus interventions in the target outcomes in the clinical training program, as well as target outcomes and competencies in the area of pre-clinical training, were recommended to be addressed.